Adherence and clinical outcomes of hypertensive patients in rural areas after receiving home pharmacy care interventions - Rikmasari, Yopi; Munarsih, Ensiwi; Alfionita, Hafiza (Jurnal Penelitian Sains, 2024)
Adherence is still a significant problem in the treatment of hypertension, so appropriate interventions are needed to overcome this condition. This study aims to determine the effect of home pharmacy care on medication adherence and clinical outcomes. This research is a pilot study using a quasi-experimental pre- and post-design with control in primary health care facilities in rural areas involving 40 hypertensive patients divided into two each 20 patients in the control and treatment groups. The MGLS questionnaire measured treatment adherence and clinical outcome by assessing blood pressure. Data were analyzed using descriptive statistics, bivariate tests using chi-square, Mann Whitney, paired t-test, and Wilcoxon signed ranks-test. At the beginning and end of the study there was no difference in the level of treatment adherence in the control group (p=0.701) while in the intervention group there was a significant difference (p=0.009). Systolic blood pressure in the control group (p=0.000) and the intervention group (p=0.004) showed a difference, while there was no difference in diastolic blood pressure in the two groups. In addition, there was no difference in achieving blood pressure targets between groups (p=0.522). The findings in this study are that home pharmacy services have the potential to increase medication adherence in rural areas but have not had an impact on reducing pressure and achieving targets.